Analisis Kualitas Pelayanan dan Kepuasan Pelanggan pada PT Dewi Wisata Provinsi Sulawesi Selatan, Indonesia: Pendekatan Kualitatif Berbasis SERVQUAL - Nur Fatima Zehra; Tiara Prisca Sabilla; Ramadhani Sanjaya; Laili Banuwa Fadila (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study aims to analyze service quality and customer satisfaction at PT Dewi Wisata, South Sulawesi Province, using a SERVQUAL-based qualitative approach. The research employed a descriptive qualitative method with data collected through in-depth interviews, non-participant observation, and documentation studies. Informants included company management, service staff, customers, and business partners involved in the company's operations. The analysis was conducted based on the five SERVQUAL dimensions, namely reliability, responsiveness,assurance, empathy, and tangibles. The results indicate that the overall service quality of PT Dewi Wisata is categorized as good and has successfully generated a high level of customer satisfaction. esponsiveness and empathy were identified as the most influential dimensions affecting customer satisfaction, reflected in prompt responses, ease of communication, friendly service, and the company's ability to provide solutions to customer problems. In addition, reliability and assurance contributed to building customer trust through accurate information and professional services, while tangibles served as supporting factors that strengthened the company's professional image. The findings suggest that high-quality service contributes positively to customer satisfaction, customer loyalty, and the sustainability of travel service businesses.